Modification of Membranes from Nylon by Microwave Radiation in Argon, Nitrogen and Atmospheric Air - D. Fazullin, Dinar; A. Kharitonova, Elena; V. Mavrin, Gennady; A. Nasyrov, Ilnar (International Journal of Engineering and Technology, 2018)
Microfiltration thin-film membranes of nylon were treated with microwave radiation within the decimeter wavelength range in air, nitrogen and argon to increase the specific productivity and the degree of the resistant oil emulsion separation due to structural transformations in the surfaces and membrane pores. After the processing of nylon membrane in air, argon and nitrogen, the specific performance of the membranes increases during the filtration of distilled water by 1.3 times. This circumstance is connected, probably with the increase of membrane pore size. And when the oil emulsion is separated, the specific productivity is increased after the treatment in air and oxygen up to 2.3 times, and after the treatment in argon it is decreased by 2 times. The decrease in performance occurs apparently due to the crosslinking of the pores and the surface layer of the membrane. It has been established that the treatment of nylon membranes with microwave radiation in air, nitrogen and argon leads to the decrease of oil emulsion separation degree, which is explained by the membrane surface etching. The worst degree of purification makes 83% and it is observed after the separation of the emulsion with the membrane treated by microwave radiation in a nitrogen atmosphere, when the loss of membrane mass after the microwave treatment was 0.69%. The purification degree from oil is reduced in the least after the treatment in argon medium - 93, and the loss of membrane mass after treatment makes 0.26%.Â